2011
DOI: 10.1002/hbm.21316
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal contributions to successful face‐name learning

Abstract: The brain mechanisms that enable us to form durable associations between different types of information are not completely understood. Although the hippocampus is widely thought to play a substantial role in forming associations, the role of surrounding cortical regions in the medial temporal lobe, including perirhinal and parahippocampal cortex, is controversial. Using anatomically constrained functional magnetic resonance imaging, we assessed medial temporal contributions to learning arbitrary associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
(99 reference statements)
2
8
0
2
Order By: Relevance
“…It is useful to then ask whether the subsequent memory effect in HPC is related to the changes in the functional connectivity of HPC with other regions in the brain. The increases in connectivity between HPC and prefrontal regions were observed in several previous studies (e.g., Hannula and Ranganath, 2009; Westerberg et al, 2011). Our study adds to these findings by showing that successful encoding is not necessarily predicted by greater HPC activation or stronger functional connectivity but rather by the changes in neural dynamics from one presentation to the next (that includes local activation and functional coupling of HPC with other brain regions).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It is useful to then ask whether the subsequent memory effect in HPC is related to the changes in the functional connectivity of HPC with other regions in the brain. The increases in connectivity between HPC and prefrontal regions were observed in several previous studies (e.g., Hannula and Ranganath, 2009; Westerberg et al, 2011). Our study adds to these findings by showing that successful encoding is not necessarily predicted by greater HPC activation or stronger functional connectivity but rather by the changes in neural dynamics from one presentation to the next (that includes local activation and functional coupling of HPC with other brain regions).…”
Section: Discussionsupporting
confidence: 79%
“…No study, however, has examined repetition-related changes in connectivity of MTL and neocortex, especially as a function of subsequent memory. The results of several previous studies that involve subsequent memory (but not the interaction of subsequent memory and priming) suggest that functional and effective connectivity between the MTL subregions (especially, HPC) and neocortex are important factors predicting the subjects’ performance on memory tasks (e.g., Ranganath et al, 2005; Hannula and Ranganath, 2009; Gagnepain et al, 2011; Westerberg et al, 2011). For example, the analysis of effective connectivity in the Gagnepain et al study revealed that successful stimulus encoding is related to the increased connectivity from the anterior aspect of the superior temporal gyrus (involved in processing of auditory stimuli) to the HPC.…”
Section: Introductionmentioning
confidence: 98%
“…At first glance, this stands in contrast to previous functional MRI studies, which have shown involvement of HC in between-item binding among younger adults (Chua et al, 2007;Qin et al, 2009;Rodrigue and Raz, 2004;Westerberg et al, 2012). However, the present results are in line with findings on older adults by Rajah et al (2010a,b), who reported no relation between HC volume and context-memory performance.…”
Section: Structural Differences In Mtl Do Not Account For Individual supporting
confidence: 79%
“…Magnetic resonance imaging (MRI) studies show that EM functioning in general draws on medialtemporal lobe (MTL) and lateral prefrontal (PFC) structures (Buckner et al, 1999;Cabeza, 2006;Dickerson and Eichenbaum, 2010;Mayes et al, 2007;Simons and Spiers, 2003;Van Petten, 2004). Findings from functional MRI studies have linked associative memory to hippocampal and item memory to parahippocampal activity, and reported greater PFC activity for associative than for item memory (Blumenfeld et al, 2011;Lepage et al, 2003;Staresina and Davachi, 2008;Westerberg et al, 2012). Structural MRI studies are less conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…As such, studies have observed greater activity in lateral PFC, especially in regions of the IFG to be related to better associative memory (Achim & Lepage, 2005b;Addis & INTRODUCTION McAndrews, 2006;Blumenfeld & Ranganath, 2006;Murray & Ranganath, 2007;Wong et al, 2013). Within the MTL, evidence suggests that greater activity in perirhinal cortex predicts better memory for associations between items and their features (e.g., between an object and its color), while greater activity in hippocampus relates to better memory performance of between-item associations (e.g., between two or more objects; Davachi & Wagner, 2002;Sperling et al, 2003a;Giovanello et al, 2004;Jackson & Schacter, 2004;Mayes et al, 2007;Staresina & Davachi, 2008;Qin et al, 2009;Westerberg et al, 2012). While this functional differentiation has been observed for different stimulus materials and types of associations, little attention has been given to regional brain responses to taskspecific factors such as type of instruction (i.e., incidental vs. intentional encoding).…”
Section: Functional Brain Factors Underlying Associative Memorymentioning
confidence: 99%